El espermatozoide, desde la eyaculación hasta la fertilización (2006)
ABSTRACT: During the last recent years there has been a great increase of information regarding the molecular mechanisms involved in the maturation of the male gamete as well as its progression from the gonad up to fertilizing the oocyte. Along this way the sperm completes its maturation adding some molecular components; additionally along this trail take place all the processes leading to activation of the sperm for the entrance into the oocyte to initiates molecular cascades for the formation of a zygote. This article, based on updated literature proposes a model that integrates known cellular and molecular interactions and pinpoints some steps still requiring further research.